Trends of Forest Management with Special Reference to Sal Forests of Bihar - Sahay, B. K. (Indian Forester, 1961)
The management problems of sal (Shorea robusta) forests under conversion to uniform, selection and coppice workings have been presented along with the application of the sampling techniques for tackling the same. The forests under conversion to uniform are still stated to be far from a uniform fcrest. Determination of increment, structure and amount of growing stock is emphasized to be necessary. Laying out tree-increment plots as representative samples and their measurement in full is suggested for finding the increment. In order to check up the forecasts of growing stock and its structure by partial enumerations, it is suggested that the girth of trees be recorded and posted in control forms at the time of their feIlings. A regeneration sampling is advocated before clear-felling the sal overwood. Adoption of a financial rotation and its adherence is explained. The growing stock and increment figures of sal forests have been compared to the French and Swiss forests. The working of Biolley’s methode du controle in Swiss forests has been described from a personal experience. The prerequisites of its adoption in other regions have been presented. It has been suggested to operate Biolley’s check method through a set of representative samples-the linear increment plots. The specific problems of over-maturity and understocking of sal forests under selection working have been explained along with the need for adjusting to an optimum structure. Two characteristic features of the coppice forests, viz., their immaturity and understacking have been described. A lesser yield is advocated in favour of capitalisation. For contending against under-stocking it is claimed that sowing of sal seeds a couple of years in advance of the coppice fellings may suffice. The role of working plans in long term investigations on the quality and quantity of timber, on production and ecological trends of forests and on efficacy of silvicultural systems has been stressed. It has been emphasized that a working plan must ensure a continuity of its provisions in order to attain the dynamic equilibrium conditions of the forest with its size.